Anticoagulant Therapy as a Tool for the Prevention of Cognitive Impairment Associated with Atrial Fibrillation - O. D. Ostroumova; A. I. Kochetkov; S. P. Korchagina; T. M. Ostroumova; M. S. Chernyaeva; A. A. Kirichenko (Рациональная фармакотерапия в кардиологии, 2019)
Atrial fibrillation (AF) is one of the most common cardiac arrhythmias in clinical practice and important additional risk factor for the development of cognitive impairment (CI) and dementia as it has been shown in recent studies. According to the Diagnostic and statistical manual of mental disorders latest revision CI refers to a decrease of one or more higher cortical functions that provide the processes of perception, storage, transformation and transmission of information compared to the premorbid level. The main hypothesis that explains the relationship between AF and dementia is the assumption that in the presence of this arrhythmia a brain substance is damaged due to microembolism and cerebral microbleeding. The high clinical significance of AF as well as CI served as a background for the development by European experts several consensus documents concerning the problem of the relationships between these conditions. In addition, they emphasize the role of anticoagulant therapy as a preventing tool for the development of stroke, which can be a factor in the CI progression in patients with AF, with particular priority to direct oral anticoagulants (DOACs). In randomized clinical trials, meta-analyses and systematic reviews have been shown that the use of DOACs, as compared to vitamin K antagonists, is a more rational strategy for preventing stroke associated with AF. Among the DOAC class, rivaroxaban is worth noticing as a drug that has a favorable efficacy profile for primary and secondary stroke prevention. Rivaroxaban distinguishing characteristics are a once daily administration as well as a calendar package which is practically important for patients with CI.